替奈普酶治疗急性缺血性卒中的研究进展及展望 Research Progress and Prospect of Tenecteplase in the Treatment of Acute Ischemic Stroke - 徐露，董漪，董强 (XU Lu, DONG Yi, DONG Qiang) (Zhongguo cuzhong zazhi)
摘要： 本文总结了替奈普酶治疗急性缺血性卒中的临床研究结果并展望了替奈普酶更广泛的临床应用和需求前景。目前的研究已经证实了在缺血性卒中发病4.5 h内，替奈普酶替代阿替普酶进行静脉溶栓治疗的实力。虽然在急性缺血性卒中的特殊人群和超再灌注时间窗治疗中，替奈普酶的有效性和安全性尚缺乏足够的循证医学证据，但目前已经开展了较多的相关研究，部分正在进行的研究将为上述患者的治疗提供更多依据。 Abstract: This paper summarizes the clinical research results of tenecteplase in the treatment of acute ischemic stroke and looks forward to the broader clinical application and demand of tenecteplase. The current study has confirmed the strength of tenecteplase as a replacement for alteplase in intravenous thrombolysis within 4.5 hours of the onset of ischemic stroke. Although there is insufficient evidence-based medical evidence on the efficacy and safety of tenecteplase in the special population of acute ischemic stroke and treatment beyond the reperfusion time window, many related studies have been conducted to date. Some ongoing research will provide more evidence for the treatment of these patients.